Glutamine potentiates cefoperazone-sulbactam activity against Pseudomonas aeruginosa by increasing membrane permeability and cellular uptake - Xiang, Jiao; Wang, Xin; Lin, Huiyin; Yang, Lifen; Huang, Xiaoxia; Chen, Yuetao; Zeng, Yingyue; Li, Shaohua; Zhao, Xianliang; Wang, Shiwen; Tao, Yuan; Fu, Huanzhe; et al. (Frontiers in Microbiology, 2025)
PurposesThe combination of an antibiotic with a metabolic reprogramming agent is anticipated to emerge as a promising therapeutic strategy against antibiotic-resistant bacteria, though this hypothesis requires validation through preclinical pharmacodynamic studies.MethodsThis study evaluated the preclinical pharmacodynamic profile of cefoperazone-sulbactam (SCF) combined with glutamine against Pseudomonas aeruginosa clinical isolates, including 54 antibiotic-sensitive (S-PA), 20 multidrug-resistant (MDR-PA), and 185 carbapenem-resistant strains (CR-PA).ResultsThe combination demonstrated synergistic efficacy in 251 cases (96.9%), equivalence in 7 (2.7%), and no interaction in 1 (0.4%) compared to SCF monotherapy. Time-kill assays, bacterial load quantification, and murine infection models consistently validated these findings, with therapeutic effects remaining stable by calcium concentrations and pH gradients. Glutamine slows the development of SCF resistance, delays the post-antibiotic effect, and reduces mutation frequency. Mechanistically, glutamine reprograms bacterial metabolism from an antibiotic-resistant to an antibiotic-sensitive state, thereby enhancing membrane permeability and increasing drug uptake. This accelerated drug influx surpasses the clearance capacity mediated by efflux pumps and enzymatic degradation, resulting in increased bacterial eradication.ConclusionThese findings suggest that the synergistic combination holds potential for developing therapeutic candidates against MDR-PA and CR-PA.